Germinação de sementes de algodoeiro provenientes de plantas submetidas a diferentes densidades larvais do curuquerê-do-algodoeiro - Michelotto, Marcos D.; Carrega, Willians C. [UNESP]; Galli, Juliana A.; Netto, Jacob Crosariol [UNESP]; Finoto, Everton L.; Busoli, Antonio C. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2012)
The cotton crop yield is directly associated with the efficient control of pests. This work evaluated the relationship of different densities of A. argillacea per plant at different cotton plant ages with seed germination of four cotton cultivars: IAC 25, Delta Opal, Fibermax 993, and Fibermax 966. A randomized block design was set up in 4x3 factorial with four replications. Densities of larvae per plant (0, 2, 4, and 6 larvae) was the major factor while plant ages (30, 60 and 90 days after emergency - DAE) the second level factor. Larvae were released on plants with 30, 60 and 90 DAE. The seeds were manually picked, for the evaluation of the germination in the laboratory using the seed viability through sand emergency method. The results showed that studied cotton cultivars differently to defoliate caused by A. argillacea larvae; the cotton development stage had more influence in the physiologic quality of the seeds than the defoliation; the germination is negatively affected when the defoliation took place at 60 DAE.
Germination of cotton seeds from plants submitted to different larval densities of cotton leafworm
Keywords: Alabama argillacea; Gossypium hirsutum; Source-drain relationship; Gossypium